Revised definition of predicted left ventricular mass using ambulatory blood pressure in healthy Korean adults - Bae Keun Kim; Enshi Xu; Bo Youl Choi; Yonggu Lee; Soon Gil Kim; Yukio Yamori; Jinho Shin (BMC, 2017)
Abstract Background Left ventricular hypertrophy is influenced by both hemodynamic and non-hemodynamic factors. Ambulatory blood pressure is correlated with left ventricular hypertrophy. We established the influences of hemodynamic and non-hemodynamic factors, including ambulatory blood pressure, on variation in left ventricular mass in healthy Korean adults. Method We included 172 subjects (male = 71, female = 101), with normal body mass index and blood pressure, in an analysis of data from the Yangpyung and Yeoju cohort studies and a tertiary cardiovascular center. Left ventricular mass was calculated using the equation: [1.04 × (IVSd + LVDd + PWTd) 3-(LDVs3)] × 0.8 + 0.6. Stroke volume was calculated (mL/beat) using Teichholz's formula. Stroke work (SW in gram-meters/beat [g-m/beat]) was computed as ambulatory systolic BP × stroke volume × 0.0144. Results Stroke work was the most important determinant associated with left ventricular mass (adjusted R 2 = 0.442, p < 0.001), independent of height2.7 and sex. In a regression model including stroke work, height,2.7 and sex, the left ventricular mass was predicted by the equation: 43.11 + 0.61 × SW (g-m/beat) + 9.21 × height2.7-13.99 × sex (male = 1, female = 2) (constant = 43.11 ± 25.88, adjusted R2 = 0.532, p < 0.001). Conclusion We examined ambulatory blood pressure, as in previous studies, and identified stroke work, height2.7, and sex as important determinants of left ventricular mass in Korean adults of normal weight and normal blood pressure. Ambulatory blood pressure is superior to clinical blood pressure for determining stroke work and predicted left ventricular mass.